Abortion rites : a social history of abortion in America - Olasky, Marvin N. (Washington, D.C : Regnery Publ, 1995)
Originally published: Wheaton,III.: Crossways Books, c1992.
Includes bibliographical references and index.
Keywords: Abortion -- United States -- History; Pro-life movement -- United States -- History